The influence of copper on tebuconazole sorption onto soils, humic substances, and ferrihydrite - Čadková, Eva; Komárek, Michael; Kaliszová, Regina; Száková, Jiřina; Vaněk, Aleš; Bordas, François; Bollinger, Jean-Claude (Environmental science and pollution research international, 2013)
The aim of this study is to investigate how the presence of Cu influences tebuconazole (Teb) sorption onto contrasting soil types and two important constituents of the soil sorption complex: hydrated Fe oxide and humic substances. Tebuconazole was used in commercial form and as an analytical-grade chemical at different Teb/Cu molar ratios (1:4, 1:1, 4:1, and Teb alone). Increased Cu concentrations had a positive effect on tebuconazole sorption onto most soils and humic substances, probably as a result of Cu-Teb tertiary complexes on the soil surfaces. Tebuconazole sorption increased in the following order of different Teb/Cu ratios 1:4>1:1>4:1>without Cu addition, with the only exception for the Leptosol and ferrihydrite. The highest K f value was observed for humic substances followed by ferrihydrite, the Cambisol, the Arenosol, and the Leptosol. The sorption of analytical-grade tebuconazole onto all matrices was lower, but the addition of Cu supported again tebuconazole sorption. The Teb/Cu ratio with the highest Cu addition (1:4) exhibited the highest K f values in all matrices with the exception of ferrihydrite. The differences in tebuconazole sorption can be attributed to the additives present in the commercial product. This work proved the importance of soil characteristics and composition of the commercially available pesticides together with the presence of Cu on the behavior of tebuconazole in soils.
Keywords: Adsorption; Humic Substances; triazoly; Chemical Phenomena; Copper; huminové látky; železité sloučeniny; látky znečišťující půdu; Pesticides; Soil Pollutants; Soil; Triazoles; půda; chemické jevy; pesticidy; Ferric Compounds; adsorpce; měď